2004
DOI: 10.1002/ptr.1550
|View full text |Cite
|
Sign up to set email alerts
|

In vivo and in vitro activities of the seed extract of Piper guineense Schum. and Thonn. against skin and gill monogenean parasites of goldfish (Carassius auratus auratus)

Abstract: Methanol extracts of the seeds of Piper guineense (Piperaceae) were active against gold fish (Carassius auratus auratus L. Pisces Cyprinidae) monogenean parasites. The seed extract of P. guineense was administered at different concentrations (0.5-2.0 mg/L) under in vivo and in vitro conditions. There was a higher efficacy of the effects of the extracts against fish parasites under in vitro situations than under in vivo. Three major compounds (piperanine, N-isobutyl (E,E)-2,4 decadienamide and Deltaalpha,beta-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…For this reason, it is necessary to test those plant extracts which could be expected to contain substances of environmental potential, and at the same time, provide adequate efficacy against Dactylogyrus. Earlier authors reported that the methanolic extracts of the seeds of Piper guineense (Piperaceae) were active against skin and gill monogenean parasites of goldfish under in vivo and in vitro conditions (Ekanem et al 2004). In our previous work, chloroform extract of Fructus arctii (dried fruits of Arctium lappa L.) exhibited a 100% anthelmintic efficacy against D. intermedius at the lowest concentration of 240.0 mg/L after 48 h of exposure (Wang et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…For this reason, it is necessary to test those plant extracts which could be expected to contain substances of environmental potential, and at the same time, provide adequate efficacy against Dactylogyrus. Earlier authors reported that the methanolic extracts of the seeds of Piper guineense (Piperaceae) were active against skin and gill monogenean parasites of goldfish under in vivo and in vitro conditions (Ekanem et al 2004). In our previous work, chloroform extract of Fructus arctii (dried fruits of Arctium lappa L.) exhibited a 100% anthelmintic efficacy against D. intermedius at the lowest concentration of 240.0 mg/L after 48 h of exposure (Wang et al 2009).…”
Section: Discussionmentioning
confidence: 98%
“…There is growing interest in using plant extracts for the treatment of human and animal disease, but little information is available on the use of the plant-derived products in the treatment of aquaculture diseases (Ekanem et al 2004). In the present study, we made a screen test using the in vivo anthelmintic efficacy assay, resulting in the selection of the Fructus Arctii from many medical plants.…”
Section: Discussionmentioning
confidence: 99%
“…Current research efforts focused on developing alternative drug formulations including medical plants. The methanol extracts of Piper guineense seeds (Piperaceae) were effective to monogenean parasites (Ekanem et al 2004). Two compounds, osthol and isopimpinellin, from Frutus cnidii have been reported to have the anthelmintic efficacy against Dactylogyrus intermedius (Wang et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Current research efforts are increasingly focused on developing alternative drug formulations including medical plants. Ekanem (Ekanem et al 2004) found that the methanol extracts of the seeds of Piper guineense (Piperaceae) were active against Dactylogyrus. Crude extracts of Radix angelicae pubescentis, Fructus bruceae, Caulis spatholobi, Semen aesculi, and Semen pharbitidis were also found to exhibit a complete elimination of all D. intermedius in goldfish (Liu et al 2010).…”
Section: Introductionmentioning
confidence: 98%